Method for preparing carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold

Combined with phenyl-2,4,6-trimethylbenzoylphosphinate lithium phosphinate by carboxymethylated xanthan gum, sulfate xanthan gum and methacrylylated gelatin Photocrosslinking technology solves the problems of insufficient mechanical properties and biodegradability of existing bone tissue engineering materials, realizes biomineralization and controllable drug release, and enhances the clinical application prospects of bone tissue repair.

CN119119515APending Publication Date: 2024-12-13WUHAN TEXTILE UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411312790.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing bone tissue engineering materials have shortcomings in terms of mechanical properties and biodegradability, which are difficult to meet the needs of clinical applications, and there is a risk of bacterial infection, so it is impossible to effectively simulate the chemical structure and mechanical properties of natural bone tissue.

Method used

Complex biomedical hydrogel scaffolds using carboxymethylated xanthan gum, sulfated xanthan gum and methacrylylated gelatin, through phenyl-2,4,6-trimethylbenzoylphosphinic acid Lithium is a photoinitiator for ultraviolet cross-linking, forming a three-dimensional network structure with high intensity, high viscosity and shear thinning, adjusting mechanical properties and porous structures, and promoting biomineralization and controlled release of drugs.

Benefits of technology

Prepare hydrogel scaffolds with good biocompatibility, biodegradability and mechanical properties, suitable for bone tissue repair and drug controlled release, can simulate the chemical structure of natural bone tissue, improve the application prospects of bone tissue engineering, and Reduce the risk of infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119515A_ABST
    Figure CN119119515A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold, and belongs to the technical field of natural high polymer materials. The preparation method comprises the following steps: respectively reacting xanthan gum with chloroacetic acid and chlorosulfonic acid, purifying to obtain carboxymethylated xanthan gum and sulfated xanthan gum, reacting gelatin with methacrylic anhydride, purifying to obtain methylacryloylated gelatin, and drying to obtain the methylacryloylated gelatin. And dissolving the obtained carboxymethylated xanthan gum, sulfated xanthan gum and methacrylated gelatin in deionized water, and carrying out optical radiation crosslinking for 10-600 seconds by using a 0.05 wt%-1 wt% phenyl-2, 4, 6-trimethylbenzoyl lithium phosphinate aqueous solution photoinitiator, so as to obtain the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold. The used raw materials are rich in source, the used photoinitiator is low in toxicity, good in water solubility and efficient, and the prepared stent material can be biomimetic mineralized, can controllably release embedded drugs, and is good in mechanical property and good in biocompatibility. The carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel can be used for preparing bone tissue repair materials, 3D printing artificial tissue scaffolds, biomedical materials and drug controlled release carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold, which belongs to the technical field of natural polymer materials. The carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel three-dimensional through-hole scaffold can be widely used in the fields of bone tissue repair and regeneration, biomedical materials, and controlled drug release. Background Art

[0002] Developing ideal artificial bone scaffold materials to replace bone transplant surgery is one of the important ways to repair bone defects. In the early days of bone tissue engineering research, people used metal materials, inorganic materials, polymer materials, or composite materials, and adopted various technologies to prepare porous biological scaffold materials similar to bone structure, and loaded cells into the biological scaffold materials to construct artificial bone tissue, and achieved success in experiments on small animal bone defect repair, thus confirming the feasibility of bone tissue engineering technology and its huge clinical application prospects. However, the structure, morphology, and biological performance of the bone tissue materials constructed in the early days are very different from those of bone tissue under physiological conditions, and cannot meet the actual needs of clinical applications. Recently, materials with bone conduction capabilities, such as b - Tricalcium phosphate is compounded with substances with bone induction ability such as bone growth factor to prepare a scaffold material with a complex structure of bionic artificial bone. Although great progress has been made in bone tissue engineering research, there are still many problems in both basic research and clinical application. Constructing bionic bone tissue similar to the chemical structure and mechanical properties of natural bone tissue and ensuring the continuous supply and discharge of nutrients, oxygen and metabolites in bionic bone tissue are key technical issues that must be solved for the clinical application of bone tissue engineering. In addition, there is a risk of bacterial infection during the repair and regeneration of bone tissue. Polymer hydrogels have a three-dimensional through-porous structure, which is suitable for simulating extracellular matrix, providing a microenvironment suitable for cell growth and maintaining normal cell phenotype and physiological function. Hydrogels are prepared using collagen or polymers with similar structures to collagen, polyanions (carboxylic acid groups or sulfonic acid groups) or polycationic polysaccharides, which are mineralized in simulated body fluids or implanted in animal tissues to form bionic bone tissue containing hydroxyapatite minerals, thereby further developing artificial bone tissue comparable to natural bone tissue.

[0003] Xanthan gum is a linear water-soluble natural polysaccharide composed of "pentasaccharide repeating units" consisting of D-glucan, D-mannose, D-glucuronic acid, acetic acid and pyruvic acid. The hydrogel prepared with xanthan gum as raw material is highly hydrophilic, non-toxic, degradable and biocompatible. It is often used as a highly absorbent resin, drug carrier and microcapsule, etc., and has broad application prospects in the biomedical field. The glucuronic acid and pyruvic acid groups on the side chains of xanthan gum and the large number of hydroxyl groups in the main chain structure of the entire molecule are conducive to the chemical modification and modification of xanthan gum. Carboxylation of xanthan gum can increase the content of carboxyl groups on the molecular chain of xanthan gum, thereby preparing carboxymethylated xanthan gum derivatives with more negative charge, more hydrophilicity and more solubility on the molecular chain. Sulfation of xanthan gum can modify sulfonic acid groups on the molecular chain of xanthan gum. The prepared sulfated xanthan gum molecular chain contains both carboxyl groups and sulfonic acid groups, and has a higher negative charge. The hydrogel molecular chain formed by chemical modification of xanthan gum will carry a large amount of negative charge. At the same time, the combination of carboxymethylated xanthan gum and sulfated xanthan gum simulates chondroitin sulfate in bone tissue to regulate the biomineralization of hydrogel scaffolds, which is more conducive to ion deposition and mineralization. Gelatin is a product obtained by collagen hydrolysis, which belongs to the category of protein macromolecules, and has good degradability and biocompatibility, and has broad application prospects in the biomedical field. However, the poor mechanical strength of gelatin limits its application. Gelatin is modified with methacrylic anhydride to contain unsaturated bonds on its molecular chain. The prepared methacrylated gelatin can be photo-crosslinked under a photoinitiator to form a hydrogel with a three-dimensional network structure. By regulating the concentration of methacrylated gelatin and the photocrosslinking time, a hydrogel with controllable mechanical properties is prepared, thereby meeting the hydrogel scaffolds with different mechanical properties. To date, methacrylated gelatin-based biomaterials have been widely studied for their physical and biochemical properties, and their applications range from controlled drug release to tissue engineering. Lithium phenyl-2,4,6-trimethylbenzoylphosphinate is a water-soluble, cell-compatible photoinitiator. Due to its higher water solubility, higher photoinitiation efficiency, and ability to rapidly initiate double bond crosslinking reactions at lower light radiation intensities, this photoinitiator is superior to Irgacure 2959 and is more suitable as a photoinitiator for photocrosslinking preparation of biomaterials and tissue engineering materials.

[0004] Based on the above analysis, combined with the advantages of carboxymethylated xanthan gum and sulfated xanthan gum and methacryloyl gelatin, the preparation of composite biomedical hydrogel scaffold materials using phenyl-2,4,6-trimethylbenzoyl lithium phosphinate as a photoinitiator and UV-crosslinked has great advantages. The hydrogel not only provides a microenvironment to maintain cell growth, but also has the characteristics of high strength, high viscosity and shear thinning, suitable for injectability and 3D printing characteristics, and is expected to be used in the fields of biomedicine and tissue engineering. In addition, the carboxymethylated xanthan gum and sulfated xanthan gum in the hydrogel have a large number of negative charges on their molecular chains, which can induce the deposition of calcium ions and phosphate ions in simulated body fluids or biological tissues in the hydrogel through electrostatic action, thereby forming a mineralized hydrogel scaffold, which has broad application prospects in the field of bone tissue repair. In addition, drugs or cell growth factors are embedded in the hydrogel scaffold, and antibiotics or cell growth factors are provided during bone repair and regeneration, which can inhibit infection and promote bone repair and regeneration. As a good scaffold material, carboxymethyl xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel not only depends on its biocompatibility and biodegradability, but more importantly, its unique chemical structure and high strength, high viscosity, shear thinning and rapid recovery of high viscosity after the shear force is removed. Carboxymethyl xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel has broad application prospects in bone tissue engineering, drug controlled release, 3D printing and other fields.

[0005] Because natural polymer composite hydrogels have great application value, their preparation and application development have become one of the current research hotspots at home and abroad. The development of ideal artificial scaffold materials to replace bone tissue transplantation surgery to repair tissue defects or lesions is one of the important topics in the field of biomaterials science and medicine. An important breakthrough in the field of 3D bioprinting is to design hydrogel materials that meet multiple bioprinting needs. At present, commercial printing gels include natural polysaccharides, proteins, and synthetic polymers, which cannot well balance the two major requirements of high strength and biodegradation safety. For example: the Chinese patent publication number is CN116236621A, the publication date is June 9, 2023, and the invention name is "A 3D printed biohybrid hydrogel and its preparation method and application". The application discloses a hydrogel made of gelatin, xanthan gum and oil gelling agent as raw materials, which has good rheological properties and meets the basic requirements of 3D printing. The disadvantage of this method is that xanthan gum and gelatin only rely on physical action, and there is no cross-linking of chemical bonds, so the mechanical strength of the composite hydrogel needs to be further improved. The Chinese patent publication number is CN115671385A, the publication date is February 3, 2023, and the invention name is "Preparation of a new 3D bioactive bone repair material". The application discloses that the surface of a polylactic acid porous scaffold is coated with polydopamine and a microsphere solution is added to adhere the microspheres to the surface of the scaffold to form a new 3D bioactive bone repair material. The disadvantage of this method is that the slow biodegradation rate of polylactic acid may lead to chronic inflammation and tissue necrosis. Therefore, the safety of the hydrogel needs to be improved. Summary of the invention

[0006] In view of the shortcomings of the above-mentioned technologies, the purpose of the present invention is to provide a method for preparing a hydrogel scaffold with abundant raw material sources, low pollution, good biocompatibility and biodegradability, good mechanical properties and biomineralization properties, controllable drug release, and 3D printable. The product obtained by this method can be quickly molded, injectable, and 3D printable.

[0007] To achieve the above purpose, the technical solution provided by the present invention is: A method for preparing a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffold, the preparation method comprising the following steps: a At 25 ℃, xanthan gum was dispersed in a mixed solution of 20 wt% NaOH and isopropanol and stirred for 2 h to form a xanthan gum-NaOH-isopropanol uniform suspension, in which the mass volume ratio of xanthan gum to isopropanol was 1:25, and the volume ratio of 20 wt% NaOH to isopropanol was 2:5; b. Dissolve chloroacetic acid in isopropanol and slowly drop it into the xanthan gum-NaOH-isopropanol uniform suspension obtained in step a, react at 60°C for 3 h, stop the reaction and cool to room temperature, then neutralize with 0.5 M acetic acid solution to pH=7, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain carboxymethylated xanthan gum, wherein the molar ratio of xanthan gum hydroxyl group to chloroacetic acid is 1:5, and the mass volume ratio of chloroacetic acid to isopropanol is 2.63:5; c. Disperse xanthan gum in dimethyl sulfoxide and stir at 25°C for 24 h to prepare a xanthan gum solution. The mass volume concentration of the obtained xanthan gum solution is 6%; d. Add pyridine to the xanthan gum solution obtained in step c, stir at 25°C for 30 min, then slowly add chlorosulfonic acid dropwise, react at 60°C for 4 h, stop the reaction and cool to room temperature, then neutralize with 5 wt% NaOH solution to pH=7, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain sulfated xanthan gum, wherein the molar ratio of pyridine to chlorosulfonic acid is 2:1, and the molar ratio of xanthan gum hydroxyl group to chlorosulfonic acid is 1:5; e. Disperse gelatin in a phosphate buffer solution with a pH of 7.4, and stir at 60°C for 60 min to prepare a gelatin solution. The mass volume concentration of the obtained gelatin solution is 10%; f. Slowly add methacrylic anhydride dropwise to the gelatin solution obtained in step e, react at 60°C for 3 h, stop heating, add phosphate buffer solution and stir, cool to 40°C, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain methacrylated gelatin, the mass volume ratio of gelatin to methacrylic anhydride is 10:1 to 5:4; g. dissolving the carboxymethyl xanthan gum obtained in step b and the sulfated xanthan gum obtained in step d in deionized water to obtain a carboxymethyl xanthan gum-sulfated xanthan gum solution with a mass volume concentration of 0.5 to 6%, wherein the mass ratio of the carboxymethyl xanthan gum to the sulfated xanthan gum is 10:1 to 1:10; h. Disperse phenyl-2,4,6-trimethylbenzoyl phosphinate lithium in deionized water, and heat in an oven at 70°C for 15 min to obtain a phenyl-2,4,6-trimethylbenzoyl phosphinate lithium aqueous solution with a concentration of 0.05 wt% to 1 wt%; i. dissolving the methacrylated gelatin obtained in step f in the 0.05 wt% to 1 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoylphosphinate lithium photoinitiator obtained in step h to obtain a methacrylated gelatin solution having a mass volume concentration of 5 to 20%; j. Add the carboxymethylated xanthan gum-sulfated xanthan gum solution obtained in step g to the methacryloyl gelatin solution obtained in step i, stir for 2 h, and cross-link under 365 nm or 405 nm light radiation for 10 s to 600 s to obtain a carboxymethylated xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel scaffold.

[0008] Due to the adoption of the above technical scheme, the technical scheme of the present invention is aimed at the chemical structure characteristics of carboxymethylated xanthan gum, sulfated xanthan gum and methacrylated gelatin, and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate is used for ultraviolet crosslinking to prepare a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold that can be biomineralized, has controlled drug release and good mechanical properties, and embeds drugs or cell growth factors in the hydrogel scaffold, and adjusts the mechanical properties of the hydrogel and the pore size of the porous structure by adjusting the content ratio of carboxymethylated xanthan gum, sulfated xanthan gum and methacrylated gelatin. Methacrylated gelatin forms a three-dimensional network structure through double bond photocrosslinking, and increasing the content of methacrylated gelatin can improve the mechanical properties of the hydrogel scaffold, thereby preparing a hydrogel scaffold with good mechanical properties. After adding a photoinitiator, methacrylated gelatin can quickly gel under ultraviolet light irradiation, and this ability of rapid gelation meets the requirements of the currently popular 3D printing technology. An important parameter of 3D printing technology is the viscosity of the precursor solution. The appropriate viscosity can ensure the successful gelation of the gel, prevent the collapse of the extruded gel before solidification, and maintain the vitality of the encapsulated cells. Carboxymethylated xanthan gum and sulfated xanthan gum have high viscosity. Carboxymethylated xanthan gum and sulfated xanthan gum are used to adjust the viscosity of the methacrylated gelatin solution to ensure the stability of the structure before photocrosslinking. Methacrylated gelatin is crosslinked by ultraviolet light using lithium phenyl-2,4,6-trimethylbenzoylphosphinate as a photoinitiator to form a three-dimensional network. The molecular chains of carboxymethylated xanthan gum and sulfated xanthan gum are interspersed in the network to prepare carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffolds. After xanthan gum is carboxymethylated and sulfated, the molecular chains are negatively charged, which can attract calcium ions to deposit on the hydrogel scaffold, and then attract phosphate ions to deposit. After multiple depositions, a good mineralization effect is achieved. The carboxyl and sulfonic acid groups in carboxymethylated xanthan gum and sulfated xanthan gum, as well as the charged groups in methacryloylated gelatin, can induce the deposition of calcium and phosphate ions in simulated body fluids or biological tissues through electrostatic effects, thereby promoting the repair and regeneration of bone tissue. Therefore, this hydrogel scaffold has broad application prospects in bone tissue engineering.

[0009] Compared with the prior art, the method for preparing the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffold of the present invention has the following advantages: The preparation method of the present invention has rich raw material sources, and the prepared hydrogel scaffold has a chemical composition similar to that of natural bone tissue. Natural human bone tissue contains about 25% by mass of organic matrix, about 65% by mass of minerals, and 10% by mass of water, wherein about 90% by mass of the organic matrix is ​​collagen, and about 10% by mass of chondroitin sulfate polymers. The biomineralization of the hydrogel scaffold is regulated by simulating chondroitin sulfate through the combination of carboxymethylated xanthan gum and sulfated xanthan gum, and methacrylated gelatin is used to replace collagen. There are double bonds on the molecular chain of methacrylated gelatin. Under the action of a photoinitiator, photocrosslinking can be performed to form a hydrogel with a three-dimensional network structure, thereby improving the mechanical properties of the hydrogel. The carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold obtained by the preparation method can control the slow release of drugs when used as a drug carrier to improve the drug efficacy; when used as a tissue engineering scaffold material, cell growth factors can be loaded and the function of simulating the extracellular matrix to control the slow release of cell growth factors can be simulated, thereby inducing cell proliferation and differentiation into regenerative tissue. Experiments show that the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold obtained by the method has a three-dimensional porous structure and has good controlled release behavior when ciprofloxacin salt is embedded. In addition, the hydrogel obtained by the method has good biomineralization properties, mechanical properties and biocompatibility. In addition, the hydrogel scaffold also has high strength and elasticity, and can be prepared into hydrogel membranes and hydrogel fibers. Therefore, the method can be widely used in the preparation of artificial bone tissue scaffold materials, and also has broad application prospects in the fields of drug controlled release, 3D bioprinting and injectable biomaterials. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a scanning electron microscope image of the surface of the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffold of Example 2 after alternate mineralization in simulated body fluid for 7 days and freeze-drying.

[0011] Figure 2 This is a scanning electron microscope image of the cross section of the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold of Example 5.

[0012] Figure 3 These are pictures of the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold of Example 5 after 0, 1 and 7 days of alternating mineralization in simulated body fluid.

[0013] Figure 4 Hydrogel scaffolds with various patterns were prepared from the carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin of Example 5. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is further described below in conjunction with specific embodiments: A method for preparing a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffold, the preparation method comprising the following steps: a At 25 ℃, xanthan gum was dispersed in a mixed solution of 20 wt% NaOH and isopropanol and stirred for 2 h to form a xanthan gum-NaOH-isopropanol uniform suspension, in which the mass volume ratio of xanthan gum to isopropanol was 1:25, and the volume ratio of 20 wt% NaOH to isopropanol was 2:5; b. Dissolve chloroacetic acid in isopropanol and slowly drop it into the xanthan gum-NaOH-isopropanol uniform suspension obtained in step a, react at 60°C for 3 h, stop the reaction and cool to room temperature, then neutralize with 0.5 M acetic acid solution, detect the pH value with pH test paper to pH=7, and obtain the product. The product obtained by the above reaction is dialyzed with distilled water and freeze-dried to obtain carboxymethylated xanthan gum, wherein the molar ratio of xanthan gum hydroxyl group to chloroacetic acid is 1:5, and the mass volume ratio of chloroacetic acid to isopropanol is 2.63:5; the zeta potential range of the obtained carboxymethylated xanthan gum is -62.5 to -98.4 mV; c. Disperse xanthan gum in dimethyl sulfoxide and stir at 25°C for 24 h to prepare a xanthan gum solution. The mass volume concentration of the obtained xanthan gum solution is 6%. In this step, a mixture of dimethyl sulfoxide and N,N-dimethylformamide can also be used to replace dimethyl sulfoxide to reduce the viscosity of the reaction system. The volume ratio of dimethyl sulfoxide to N,N-dimethylformamide is 1:1. d. Add pyridine to the xanthan gum solution obtained in step c, stir at 25°C for 30 min, then slowly add chlorosulfonic acid dropwise, wherein the molar ratio of pyridine to chlorosulfonic acid is 2:1, and the molar ratio of xanthan gum hydroxyl to chlorosulfonic acid is 1:5, react at 60°C for 4 h, stop the reaction and cool to room temperature, then neutralize with 5 wt% NaOH solution, detect its pH value with pH test paper to pH=7, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain sulfated xanthan gum. In this step, the neutralized reaction mixture can also be precipitated with ethanol, vacuum filtered, and the solid product is collected, washed with ethanol three times, added with deionized water and stirred, placed in a dialysis bag for dialysis, and freeze-dried to obtain sulfated xanthan gum; e. Disperse gelatin in a phosphate buffer solution with a pH of 7.4, and stir at 60°C for 60 min to prepare a gelatin solution. The mass volume concentration of the obtained gelatin solution is 10%; f. Slowly add methacrylic anhydride dropwise to the gelatin solution obtained in step e, react at 60 °C for 3 h, stop heating, add phosphate buffer solution and stir, cool to 40 °C, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain methacrylic gelatin. The mass volume ratio of gelatin to methacrylic anhydride is 10:1 to 5:4, and the degree of substitution of the obtained methacrylic gelatin is 54% to 82%; g. dissolving the carboxymethyl xanthan gum obtained in step b and the sulfated xanthan gum obtained in step d in deionized water to obtain a carboxymethyl xanthan gum-sulfated xanthan gum solution with a mass volume concentration of 0.5 to 6%, wherein the mass ratio of the carboxymethyl xanthan gum to the sulfated xanthan gum is 10:1 to 1:10; h. dispersing phenyl-2,4,6-trimethylbenzoyl lithium phosphinate in deionized water, and heating in an oven at 70°C for 15 min to obtain a phenyl-2,4,6-trimethylbenzoyl lithium phosphinate aqueous solution with a concentration of 0.05 wt% to 1 wt%; i. dissolving the methacrylated gelatin obtained in step f in the 0.05 wt% to 1 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoylphosphinate lithium photoinitiator obtained in step h to obtain a methacrylated gelatin solution with a mass volume concentration of 5 to 20%. This step needs to be heated in an oven at 70°C for 15 min, and the methacrylated gelatin is melted and then dissolved; j. Add the carboxymethylated xanthan gum-sulfated xanthan gum solution obtained in step g to the methacrylylated gelatin solution obtained in step i, stir at 35 °C for 2 h, and crosslink under 365 nm or 405 nm light radiation for 10 s~600 s, to obtain a carboxymethylated xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel scaffold; to embed ciprofloxacin hydrochloride in the carboxymethylated xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel scaffold, and to study the release behavior of ciprofloxacin hydrochloride embedded in the hydrogel; to alternately soak the hydrogel scaffold in simulated body fluid containing calcium ions and phosphate ions, to wash the soaked scaffold with deionized water, to obtain the mineralized hydrogel scaffold after freeze-drying, to determine the chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffold before and after mineralization by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis, to study the rheological behavior of the hydrogel before and after mineralization by rheometer, and to observe the morphology and element content of the hydrogel before and after mineralization by scanning electron microscopy. Example 1

[0015] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 8 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.15 g of carboxymethylated xanthan gum and 0.15 g of sulfated xanthan gum were dissolved in 4 ml of deionized water, and magnetically stirred for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 0.5 g of methacryloyl gelatin was dissolved in a 0.05 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked under ultraviolet light for 60 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy. Example 2

[0016] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 4 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.50 g of carboxymethylated xanthan gum and 0.05 g of sulfated xanthan gum were dissolved in 4 ml of deionized water, and magnetically stirred for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 0.5 g of methacryloyl gelatin was dissolved in a 0.5 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked under ultraviolet light for 10 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy. Example 3

[0017] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 1 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.03 g of carboxymethylated xanthan gum and 0.30 g of sulfated xanthan gum were dissolved in 4 ml of deionized water, and magnetically stirred for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 2.0 g of methacryloyl gelatin was dissolved in a 1 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked with ultraviolet light for 600 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy. Example 4

[0018] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 8 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.40 g carboxymethylated xanthan gum and 0.20 g sulfated xanthan gum were dissolved in 4 ml deionized water, and magnetically stirred for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 0.9 g methacryloyl gelatin was dissolved in a 0.1 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked with ultraviolet light for 100 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy. Example 5

[0019] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 8 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.15 g of carboxymethylated xanthan gum and 0.15 g of sulfated xanthan gum were dissolved in 4 ml of deionized water, and magnetically stirred for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 1.2 g of methacryloyl gelatin was dissolved in a 0.3 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked under ultraviolet light for 60 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy. Example 6

[0020] 4.0 g of xanthan gum was dispersed in 140 mL of a mixed solution of 20 wt% NaOH and isopropanol, and stirred at 25 °C for 2 h to form a uniform suspension. 22.28 g of chloroacetic acid was dissolved in isopropanol and slowly added dropwise to the xanthan gum suspension system, and reacted at 60 °C for 3 h. After stopping the reaction, cool to room temperature, neutralize with 0.5 M acetic acid solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain carboxymethyl xanthan gum; disperse 3.0 g of xanthan gum in 50 mL of dimethyl sulfoxide, stir at 25 ° C for 24 h, add 15.6 mL of pyridine, stir at 25 ° C for 30 min, add 6.5 mL of chlorosulfonic acid dropwise, react at 60 ° C for 4 h, stop the reaction, cool to room temperature, neutralize with 5 wt% NaOH solution to pH = 7, dialyze the above product with distilled water, and freeze-dry to obtain sulfated xanthan gum; dissolve 10 g of gelatin in 100 mL of phosphate buffer solution with pH = 7.4, stir at 60 ° C for 60 min, add 8 mL of methacrylic anhydride dropwise to the gelatin solution, react at 60 ° C for 3 h, stop heating, add 300 mL of phosphate buffer solution, stir, cool to 40 ℃, the reaction product was dialyzed with distilled water and freeze-dried to obtain methacryloyl gelatin; 0.04 g carboxymethylated xanthan gum and 0.01 g sulfated xanthan gum were dissolved in 4 ml deionized water, and magnetic stirring was performed for 12 h to obtain a carboxymethylated xanthan gum-sulfated xanthan gum solution; 1.2 g methacryloyl gelatin was dissolved in a 0.5 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate under light-proof conditions, and heated in an oven at 70 ℃ for 15 min. After complete dissolution, a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was obtained, which was cooled to room temperature, and the carboxymethylated xanthan gum-sulfated xanthan gum solution was transferred to a mixed aqueous solution of methacryloyl gelatin and phenyl-2,4,6-trimethylbenzoyl lithium phosphinate, stirred at 35 ℃ for 2 h, and heated with 10 mW / cm 2 The hydrogel scaffolds were photocrosslinked with ultraviolet light for 100 s to obtain carboxymethylated xanthan gum-sulfated xanthan gum-methacrylylated gelatin hydrogel scaffolds. The hydrogel scaffolds were alternately immersed in simulated body fluids containing calcium ions and phosphate ions. The immersed scaffolds were washed with deionized water and freeze-dried to obtain mineralized hydrogel scaffolds. The chemical structure, crystal structure and thermogravimetric analysis curve of the hydrogel scaffolds before and after mineralization were determined by infrared spectrometer, X-ray diffractometer and thermogravimetric analysis. The rheological behavior of the hydrogel before and after mineralization was studied by rheometer. The morphology and element content of the hydrogel before and after mineralization were observed by scanning electron microscopy.

Claims

1. A method for preparing a carboxymethylated xanthan gum-sulfated xanthan gum-methacrylated gelatin hydrogel scaffold, characterized in that: The method described is carried out according to the following steps: a At 25 °C, xanthan gum was dispersed in a mixed solution of 20 wt% NaOH and isopropanol, and stirred for 2 h to form a xanthan gum-NaOH-isopropanol uniform suspension, wherein the mass volume ratio of xanthan gum to isopropanol was 1:25, and the volume ratio of 20 wt% NaOH to isopropanol was 2:5; b. Dissolve chloroacetic acid in isopropanol and slowly drop it into the xanthan gum-NaOH-isopropanol uniform suspension obtained in step a, react at 60°C for 3 h, stop the reaction and cool to room temperature, then neutralize with 0.5 M acetic acid solution to pH=7, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain carboxymethylated xanthan gum, wherein the molar ratio of xanthan gum hydroxyl group to chloroacetic acid is 1:5, and the mass volume ratio of chloroacetic acid to isopropanol is 2.63:5; c. Disperse xanthan gum in dimethyl sulfoxide and stir at 25°C for 24 h to prepare a xanthan gum solution. The mass volume concentration of the obtained xanthan gum solution is 6%; d. Add pyridine to the xanthan gum solution obtained in step c, stir at 25°C for 30 min, then slowly add chlorosulfonic acid dropwise, react at 60°C for 4 h, stop the reaction and cool to room temperature, then neutralize with 5 wt% NaOH solution to pH=7, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain sulfated xanthan gum, wherein the molar ratio of pyridine to chlorosulfonic acid is 2:1, and the molar ratio of xanthan gum hydroxyl group to chlorosulfonic acid is 1:5; e. Disperse gelatin in a phosphate buffer solution with a pH of 7.4, and stir at 60°C for 60 min to prepare a gelatin solution. The mass volume concentration of the obtained gelatin solution is 10%; f. Slowly add methacrylic anhydride dropwise to the gelatin solution obtained in step e, react at 60°C for 3 h, stop heating, add phosphate buffer solution and stir, cool to 40°C, dialyze the product obtained by the above reaction with distilled water, and freeze-dry to obtain methacrylated gelatin, the mass volume ratio of gelatin to methacrylic anhydride is 10:1 to 5:4; g. dissolving the carboxymethyl xanthan gum obtained in step b and the sulfated xanthan gum obtained in step d in deionized water to obtain a carboxymethyl xanthan gum-sulfated xanthan gum solution with a mass volume concentration of 0.5 to 6%, wherein the mass ratio of the carboxymethyl xanthan gum to the sulfated xanthan gum is 10:1 to 1:10; h. dispersing phenyl-2,4,6-trimethylbenzoyl lithium phosphinate in deionized water, and heating in an oven at 70°C for 15 minutes to obtain a phenyl-2,4,6-trimethylbenzoyl lithium phosphinate aqueous solution with a concentration of 0.05 wt% to 1 wt%; i. dissolving the methacrylated gelatin obtained in step f in the 0.05 wt% to 1 wt% aqueous solution of phenyl-2,4,6-trimethylbenzoylphosphinate lithium photoinitiator obtained in step h to obtain a methacrylated gelatin solution having a mass volume concentration of 5 to 20%; j. Add the carboxymethylated xanthan gum-sulfated xanthan gum solution obtained in step g to the methacryloyl gelatin solution obtained in step i, stir for 2 h, and cross-link under 365 nm or 405 nm light radiation for 10 s to 600 s to obtain a carboxymethylated xanthan gum-sulfated xanthan gum-methacryloyl gelatin hydrogel scaffold.